The Effects of BIM Maturity Levels on Modularization and Standardization in the Construction Industry: A Systematic Literature Review and Case Studies - Bayzidi E; Kordestani Ghalenoei N; Babaeian Jelodar M (MDPI (Basel; Switzerland), 2025)
The increasing demand for efficient, sustainable, and coordinated construction practices has intensified interest in the integration of digital tools such as Building Information Modelling (BIM) with modularization and standardization strategies. This study aims to examine the relationship among BIM maturity levels, modularization grades, and standardization levels, and to assess their combined impact on construction project outcomes. A mixed-methods approach, including a systematic literature review and New Zealand-based case studies, is used to develop and validate an evaluative framework. The SLR identifies key themes and determinants, while the case studies provide empirical evidence on the interactions between BIM maturity levels, modularization grades, and standardization levels. The study identifies that higher BIM maturity levels significantly enhance modularization and standardization practices. Advanced BIM capabilities foster improved design coordination, collaboration, and data management, leading to more efficient construction processes. A guideline for mapping BIM maturity against standardization levels is proposed to assist stakeholders in evaluating and optimizing project outcomes. This research offers a novel perspective on integrating BIM maturity with modularization and standardization practices. While it is applied in the New Zealand context, the proposed framework and methodology are designed to be transferable to international settings. It provides actionable insights for policymakers and industry stakeholders seeking to refine standards, promote BIM adoption, and enhance construction project efficiency worldwide.
Keywords: Building Information Modelling; BIM maturity levels; construction industry; modularization grades; standardization levels; technology integration